Casting a giant shadow : the transnational shaping of Israeli cinema - Harris, Rachel S. (Rachel Sylvia), 1977-; Chyutin, Dan (Bloomington, Indiana : Indiana University Press, 2021)
"Film came to the territory that eventually became Israel not long after the medium was born. Casting a Giant Shadow is a collection of articles that embraces the notion of transnationalism to consider the limits of what is "Israeli" within Israeli cinema. As the State of Israel developed, so did its film industries. Moving beyond the early films of the Yishuv, which focused on the creation of national identity, the industry and its transnational ties became more important as filmmakers and film stars migrated out and foreign films, filmmakers, and actors came to Israel to take advantage of high-quality production values and talent. This volume, edited by Rachel Harris and Dan Chyutin, uses the idea of transnationalism to challenge the concept of a singular definition of Israeli cinema. Casting a Giant Shadow offers a new understanding of how cinema has operated artistically and structurally in terms of funding, distribution, and reception. The result is a thorough investigation of the complex structure of the transnational and its impact on national specificity when considered on the global stage"--
Israeli Cinema Beyond the National : An Introduction / Rachel S. Harris and Dan Chyutin -- I Have a Great Passion for Americans : The Juggler and the Question of National Cinema / Dan Chyutin -- Longing for Hollywood : Israeli Beauties on International Film Stages in the 1950s and 1960s / Julie Grimmeisen -- New Frontiers : Creating a Nation through the Israeli Western / Rachel S. Harris -- The Rust of Time : The Apparition of Memory in David Greenberg's Sha'ar Ha'guy (1965) and Much'shar Bli Rosh (1963) / Shmulik Duvdevani and Anat Dan -- Transnational Imaginings in Salt of This Sea (2008) and Villa Touma (2015) / Ariel M. Sheetrit -- Here and There, Now and Then : Nations and Their Relations in Recent Palestinian Cinema / Mary N. Layoun -- Five Broken Cameras and the Metonymic Sixth Camera : Time, Narrative, and Subjectivities in Emad Burnat and Guy Davidi's 5 Broken Cameras / Yaron Shemer -- Moments of Innocence and Fracture : Fantasy and Reality in Two Documentary Visits to Israel / Ohad Landesman -- Two Israelis in the "Mecca of Motion Pictures" : Golan, Globus, and Cannon Film's Transnational Enterprise / Zachary Ingle -- A Chance to Hear Some Hebrew : American Jewish Film Festivals and the Transnational Flow of Israeli Film / Josh Beaty -- Perpetuating Victimhood as a Jewish Identity? : The Case of Popular Israeli Cinema Today / Yaron Peleg -- Of National Homes and Despotic Symbols : Network Narrative Films, Global Cities, and Local Crossings of Paths / Nava Dushi -- Fantasies of Other Desires : Homonationalism and Self-Othering in Contemporary Israeli Queer Cinema / Raz Yosef and Boaz Hagin -- Hagar Ben Asher's The Slut as the First Israeli Transnational Feminist Film Text / Yael Munk -- Encounters and Interspaces : The Place of Germany and Germans in Israeli Cinema / Tobias Ebbrecht-Hartmann -- Blood, Sweat, and Tears: The Rise of Israel's New Extremism / Neta Alexander -- The Exchange : Reinventing Israeliness through Koreanness / Pablo Utin.
Includes bibliographical references and index.
Online resource; title from PDF title page (ProQuest Ebook Central platform, viewed October 17, 2023).
JSTOR
Keywords: Motion pictures -- Israel; Motion picture industry -- Israel; Motion pictures and transnationalism -- Israel; Nationalism in motion pictures; Cinéma -- Industrie -- Israël.; Cinéma et transnationalisme -- Israël.; Nationalisme au cinéma.; Cinéma -- Israël.; PERFORMING ARTS -- Film & Video -- History & Criticism; Motion picture industry; Motion pictures; Motion pictures and transnationalism; Nationalism in motion pictures; Israel; Electronic books; Film criticism; Critiques cinématographiques.